2013
DOI: 10.1021/nl4003969
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical or Not? Effect of the Length Scale and Hierarchy of the Surface Roughness on Omniphobicity of Lubricant-Infused Substrates

Abstract: Lubricant-infused textured solid substrates are gaining remarkable interest as a new class of omni-repellent nonfouling materials and surface coatings. We investigated the effect of the length scale and hierarchy of the surface topography of the underlying substrates on their ability to retain the lubricant under high shear conditions, which is important for maintaining nonwetting properties under application-relevant conditions. By comparing the lubricant loss, contact angle hysteresis, and sliding angles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
421
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 439 publications
(438 citation statements)
references
References 46 publications
14
421
2
1
Order By: Relevance
“…The TP we used was covalently coupled to the surface by silane chemistry that is used in dental adhesives, but other reactive groups could be utilized to generate TP layers 26 . The LP perfluorodecalin used here has been previously included in an FDA-approved blood substitute; however, we have found that a variety of LPs, medical grade and non-medical grade, also can repel blood when integrated into a TLP coating (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TP we used was covalently coupled to the surface by silane chemistry that is used in dental adhesives, but other reactive groups could be utilized to generate TP layers 26 . The LP perfluorodecalin used here has been previously included in an FDA-approved blood substitute; however, we have found that a variety of LPs, medical grade and non-medical grade, also can repel blood when integrated into a TLP coating (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). These TLP-coated smooth surfaces also were equally as effective as porous materials (expanded PTFE, colloidal monolayers and nanostructured boehmite) that were infused with LP, the original SLIPS technology (e.SLIPS and B.SLIPS, respectively), which have previously been shown to repel crude oil and ice, as well as anticoagulated animal blood 20,26,27 . Additionally, an acrylic sheet and a commercial PP tube modified with the TLP coating showed no blood adhesion after immersion in human blood, which was in stark contrast to the control…”
Section: Supplementary Movie 1)mentioning
confidence: 99%
“…Since these properties can all be incorporated into a single coating, new approaches of forming such coatings on a broad variety of materials, such as metals, ceramics, or polymers, are being developed. 91 The slippery surfaces can potentially be used in a wide variety of industrial and medical applications and environments and may provide alternative solutions for designing materials with special wettability that could not be addressed by conventional lotus leaf-inspired surfaces. 92 Ultimately, the widespread application of any of the aforementioned bioinspired interfacial materials is dictated by their cost, scalability, and robustness, which are important for their practical use on a large scale and accessibility to people with low budgets and around the world.…”
Section: Discussionmentioning
confidence: 99%
“…However, the requirements to sustain repellency throughout an endoscopic procedure are extremely challenging because (i) direct contact with proteins, cells, and bacteria, as well as the formation of blood clots upon contact with an abiotic surface, compromise the performance of superhydrophobic surfaces (11,12), and (ii) their transparency is not easily achievable. Recently, liquid-infused coatings, consisting of a porous structure infiltrated with a lubricant, have emerged as a new, alternative strategy for repellent materials (11,(13)(14)(15)(16)(17). The formation of a stable lubricant overlayer on the surface creates a dynamic slippery barrier that protects the underlying substrate from direct contact with polluted media, thus drastically lowering the adsorption of various serious contaminants including bacteria (18,19) and proteins (20)(21)(22).…”
Section: Significancementioning
confidence: 99%